Study on the Reparative Effect of PEGylated Growth Hormone on Ovarian Parameters and Mitochondrial Function of Oocytes From Rats With Premature Ovarian Insufficiency - Feng, Penghui; Xie, Qiu; Liu, Zhe; Guo, Zaixin; Tang, Ruiyi; Yu, Qi (Frontiers in Cell and Developmental Biology, 2021)
Premature ovarian insufficiency (POI) is a heterogeneous disorder and lacks effective interventions in clinical applications. This research aimed to elucidate the potential effects of recombinant human PEGylated growth hormone (rhGH) on follicular development and mitochondrial function in oocytes as well as ovarian parameters in POI rats induced by the chemotherapeutic agent. The impacts of rhGH on ovarian function before superovulation on follicles, estrous cycle, and sex hormones were evaluated. Oocytes were retrieved to determine oocyte quality and oxidative stress parameters. Single-cell sequencing was applied to investigate the latent regulatory network. This study provides new evidence that a high dosage of rhGH increased the number of retrieved oocytes even though it did not completely restore the disturbed estrous cycle and sex hormones. rhGH attenuated the apoptosis of granulosa cells and oxidative stress response caused by reactive oxygen species (ROS) and mitochondrial superoxide. Additionally, rhGH modulated the energy metabolism of oocytes concerning the mitochondrial membrane potential and ATP content but not mtDNA copy numbers. Based on single-cell transcriptomic analysis, we found that rhGH directly or indirectly promoted the balance of oxidative stress and cellular oxidant detoxification. Four hub genes, Pxmp4, Ehbp1, Mt-cyb, and Enpp6, were identified to be closely related to the repair process in oocytes as potential targets for POI treatment.